(How) does 1,3,5-triethylbenzene scaffolding work? Analyzing the abilities of 1,3,5-triethylbenzene- and 1,3,5-trimethylbenzene-based scaffolds to preorganize the binding elements of supramolecular hosts and to improve binding of targets - Wang, Xing; Hof, Fraser (Beilstein Journal of Organic Chemistry, 2012)
1,3,5-triethylbenzenes have been widely used as supramolecular templates to organize molecular-recognition elements. It is believed that the steric-gearing effect of the 1,3,5-triethylbenzene template directs the binding elements toward the same face of the central ring, hence increasing the binding affinity. At the same time the 1,3,5-trimethylbenzene scaffold, without steric-gearing effects, has also been found to improve the binding affinities of hosts compared to the unsubstituted analogues. By studying experimental data from the literature and the Cambridge Structural Database, as well as by conducting computational studies of representative structures, we concluded that the steric gearing offered by the ethyl groups confers some energetic advantage over the methyl groups, but the size of this advantage can be small and is dependent on the groups involved.
Keywords: binding affinity; entropy; molecular recognition; scaffolds; supramolecular hosts; triethylbenzene; trimethylbenzene

Modern physical organic chemistry - Anslyn, E. V.; Dougherty, D. A. (University Science Books, 2005)

(untitled) - Tsuzuki, S.; Fujii, A. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Cram, D. J. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Seel, C.; Vögtle, F. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Hennrich, G.; Anslyn, E. V. (Chem.–Eur. J., 2002)

(untitled) - Iverson, D. J.; Hunter, G.; Blount, J. F.; Damewood, J. R., Jr; Mislow, K. (J. Am. Chem. Soc., 1981)

(untitled) - MacNicol, D. D.; Hardy, A. D. U.; Wilson, D. R. (Nature, 1977)

(untitled) - Stack, T. D. P.; Hou, Z.; Raymond, K. N. (J. Am. Chem. Soc., 1993)

(untitled) - Metzger, A.; Lynch, V. M.; Anslyn, E. V. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Wallace, K. J.; Belcher, W. J.; Turner, D. R.; Syed, K. F.; Steed, J. W. (J. Am. Chem. Soc., 2003)

(untitled) - Sato, K.; Arai, S.; Yamagishi, T. (Tetrahedron Lett., 1999)

(untitled) - Fahlbusch, T.; Frank, M.; Schatz, J.; Schmaderer, H. (Eur. J. Org. Chem., 2006)

(untitled) - Kim, S.-G.; Ahn, K. H. (Chem.–Eur. J., 2000)

(untitled) - Mazik, M.; Radunz, W.; Boese, R. (J. Org. Chem., 2004)

(untitled) - Kim, J.; Raman, B.; Ahn, K. H. (J. Org. Chem., 2006)

(untitled) - Ahn, K. H.; Kim, S.-G.; Jung, J.; Kim, K.-H.; Kim, J.; Chin, J.; Kim, K. (Chem. Lett., 2000)

(untitled) - Yoon, J.; Kim, S. K.; Singh, N. J.; Kim, K. S. (Chem. Soc. Rev., 2006)

(untitled) - Yun, S.; Ihm, H.; Kim, H. G.; Lee, C.-W.; Indrajit, B.; Oh, K. S.; Gong, Y. J.; Lee, J. W.; Yoon, J.; Lee, H. C.; Kim, K. S. (J. Org. Chem., 2003)

(untitled) - Kilway, K. V.; Siegel, J. S. (Tetrahedron, 2001)

(untitled) - Chang, C. A.; Chen, W.; Gilson, M. K. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Pickett, S. D.; Sternberg, M. J. E. (J. Mol. Biol., 1993)

(untitled) - Rekharsky, M.; Inoue, Y.; Tobey, S.; Metzger, A.; Anslyn, E. (J. Am. Chem. Soc., 2002)